The upward shift in altitude of pine mistletoe (Viscum album ssp austriacum) in Switzerland - the result of climate warming? - Dobbertin, Matthias; Hilker, Nadine; Rebetez, Martine; Zimmermann, Niklaus E; Wohlgemuth, Thomas; Rigling, Andreas (My University, 2005)
Pine mistletoe (Viscum album ssp. austriacum) is common in natural Scots pine (Pinus sylvestris L.) forests in the alpine Rhone Valley, Switzerland. This semi-parasite, which is regarded as an indicator species for temperature, increases the drought stress on trees and may contribute to the observed pine decline in the region. We recorded mistletoes on representative plots of the Swiss National Forest Inventory ranging from 450 to 1,550 m a.s.l. We found mistletoe on 37% of the trees and on 56% of all plots. Trees infested with mistletoe had a significantly higher mortality rate than non-infested trees. We compared the current mistletoe occurrence with records from a survey in 1910. The current upper limit, 1,250 m, is roughly 200 m above the limit of 1,000-1,100 m found in the earlier survey 100 years ago. Applying a spatial model to meteorological data we obtained monthly mean temperatures for all sites. In a logistic regression mean winter temperature, pine proportion and geographic exposition significantly explained mistletoe occurrence. Using mean monthly January and July temperatures for 1961-1990, we calculated Skre's plant respiration equivalent (RE) and regressed it against elevation to obtain the RE value at the current mistletoe elevation limit. We used this RE value and temperature from 1870-1899 in the regression and found the past elevation limit to be at 1,060 m, agreeing with the 1910 survey. For the predicted temperature rise by 2030, the limit for mistletoe would increase above 1,600 m altitude.
Keywords: pine mistletoe; respiration equivalent; logistic regression; pine; decline; climate change; TREE MORTALITY; DWARF MISTLETOE; TEMPERATURE; GROWTH; STANDS; 20TH-CENTURY; COLORADO; RING